The Influence of Transformational Leadership and HRM Practices on Organization Performance: Organization Trust as a Mediator - Andri Ajis; Auna Rosmala Mansyur; Yolanda Dwi Prastica; Nur Damayanti (Budapest International Research and Critics University, 2022)
In today's competitive world, businesses must constantly innovate and improve. As a result, the company is constantly striving to improve its performance to achieve company goals. Organizational performance is an important issue, and the antecedents of organizational performance have been explored in various studies. This study examines the mediating effect of organizational trust in the relationship between transformational leadership, HRM practices, and organizational performance. This study was measured by questionnaires, and the results of hypothesis testing were carried out with Smart PLS 3.0 on 315 respondents at PT. Taspen (Persero). The results show that transformational leadership has no direct effect on organizational performance. Meanwhile, HRM practices are directly significant to organizational performance. Organizational trust was found to mediate the relationship between transformational leadership, HRM practices, and organizational performance. The results of this study have implications for organizations that can help policy makers, especially at PT Taspen (Persero), to better understand what factors can affect organizational performance. Further research more deeply factor that influence work efficiency such as organization culture, motivation, knowledge management.